The Art of Teaching Tongues - Deborah Idowu (Vernacular: New Connections in Language, Literature, & Culture, 2025)
The poem describes the multifaceted role and experience of a language teacher through metaphors and imagery. The poem presents language instruction as both an art and a sacred duty, employing metaphors of a keeper of keys, shepherd, and smith to illustrate the teacher's diverse responsibilities. Through four-line stanzas with consistent rhyme schemes, the work progresses from describing the technical aspects of language instruction to revealing its deeper purpose of fostering cross-cultural understanding. An instructor's personal investment in teaching is portrayed through intimate first-person narration, while imagery of growth, construction, and transformation underscores the developmental nature of language acquisition. The poem is written to be the anthem of the language teacher.
Keywords: Teaching; Language; Learning; Language Teacher